A new species of karst forest Bent-toed Gecko (genus Cyrtodactylus Gray) not yet threatened by foreign cement companies and a summary of Peninsular Malaysia’s endemic karst forest herpetofauna and the need for its conservation - Grismer, L. Lee; Wood, P. L., Jr.; Anuar, Shahrul; Davis, H. R.; Cobos, A. J.; Murdoch, M. L. (Zootaxa, 2016)
A new species of Bent-toed Gecko, Cyrtodactylus gunungsenyumensis sp. nov. of the sworderi complex, is described from Hutan Lipur Gunung Senyum, Pahang, Peninsular Malaysia and is differentiated from all other species in the sworderi complex by having a unique combination of characters including a maximum SVL of 74.7 mm; low, rounded, weakly keeled, body tubercles; 34–40 paravertebral tubercles; weak ventrolateral body fold lacking tubercles; 38–41 ventral scales; an abrupt transition between the posterior and ventral femoral scales; 20–23 subdigital lamellae on the fourth toe; enlarged femoral scales; no femoral or precloacal pores; no precloacal groove; wide caudal bands; and an evenly banded dorsal pattern. Cyrtodactylus gunungsenyumensis sp. nov. is a scansorial, karst forest-adapted specialist endemic to the karst ecosystem surrounding Gunung Senyum and occurs on the vertical walls of the limestone towers as well as the branches, trunks, and leaves of the vegetation in the associated karst forest. Cyrtodactylus gunungsenyumensis sp. nov. is the seventh species of karst forest-adapted Cyrtodactylus and the sixteenth endemic species of karst ecosystem reptile discovered in Peninsular Malaysia in the last seven years from only 12 different karst forests. This is a clear indication that many species remain to be discovered in the approximately 558 isolated karst ecosystems in Peninsular Malaysia not yet surveyed. These data continue to underscore the importance of karst ecosystems as reservoirs of biodiversity and microendemism and that they constitute an important component of Peninsular Malaysia’s natural heritage and should be protected from the quarrying interests of foreign industrial companies.